Gareth evans’s argument against vague identity - Odrowąż-Sypniewska, Joanna (Logic and Logical Philosophy, 2003)
In the paper Evans’s argument concerning indeterminate identity statements is presented and discussed. Evans’s paper in which he formulated his argument is one of the most frequently discussed papers concerning identity. There are serious doubts concerning what Evans wanted to prove by his argument. Theorists have proposed two competing and incompatible interpretations. According to some, Evans purposefully constructed an invalid argument in order to demonstrate that the vague objects view cannot diagnose the fallacy and is therefore untenable. According to others, Evans wanted to formulate a (valid) argument to the effect that there cannot be vague identity statements whose vagueness is due solely to the existence of vague objects. As it has been argued, if it is the former interpretation which is correct, than the argument really is invalid, but it is doubtful whether it achieves its aim. It might be claimed that “the vague objects view” it refutes is not the view that most vague objects theorists hold. The main part of the paper is devoted to the second interpretation and the discussions concerning the validity of the argument on this interpretation. It appears that the vague objects theorist is in a position to object to the validity of every single step of the proof.